Assessment of multiphase boiling models: For modelling of heat and mass transfer in an aero engine steam vaporizer tube - Blom Larsen, Alexander (My University, 2024)
The growing aviation industry is transitioning towards more sustainable and efficient aero engines, with many aerospace companies investigating the use of heat exchanger technology to reduce specific fuel consumption (SFC) and enhance thermal efficiency. Multiphase boiling models enable the analysis of flow behaviour and performance of heat exchanger systems, including mass, momentum, and heat transfer. This thesis provides a comprehensive analysis of the Lee and Thermal Phase Change boiling models and their available sub models in terms of their robustness and accuracy in modelling fully phase inverted boiling scenarios. A survey of the available sub-models was conducted to conclude how different modelling approaches affects the results. In terms of the Interfacial Area Concentration (IAC) modelling, the interfacial area transport equation approach promoted boiling for the Lee model, while inhibiting it for the Thermal Phase Change model. The algebraic model displayed better convergence behaviour. As for heat transfer modelling, the double-resistance approach yielded more accurate wall temperatures than the single-resistance approach. Regarding turbulence modelling, solving two sets of turbulence equations showed negligible differences compared to a single set. The k − ω SST model was deemed more appropriate for this case compared to the standard k − ε model. In terms of the interfacial momentum transfer (force) modelling, the results showed that only modelling the drag and turbulent dispersion forces affected the results non-trivially. When compared to experiments, in all cases the numerical results matched experimental data poorly, although the Thermal Phase Change model was seen to outperform the Lee model relatively speaking. Tuning the model coefficients showed some improvement, especially for the Lee model, but not for the Thermal Phase Change model. Finally, in order to assess any impact of explicit modelling of the tube walls on the overall veracity of the numerical results, including the tube wall thicknesses explicitly was to seen to improve the performance of both the Lee and Thermal Phase Change models, particularly when used in conjunction with the double-resistance thermal resistance approach.
Keywords: Heat transfer; boiling; multiphase; CFD; Eulerian multiphase; Conjugate heat transfer